Salvia macrosiphon seeds and seed oil: pharmacognostic, anti-inflammatory and analgesic properties - A. Hamedi; A. Jamshidzadeh; S. Ahmadi; M. Sohrabpour; M.M. Zarshenas (Iranian Society of Pharmacognosy, 2016)
Background and objectives:Wild Sage(Salvia macrosiphon Boiss.) known as "Marvak" in Persian is one of the polymorphic and abundant plants of Lamiaceae. The plants whole seeds usually soaked or boiled in hot water are widely used for inflammatory ailments in folk medicine. Documents have shown that there is scant information on the chemical constituents of this plant seeds. The current study was carried out to assess the phytochemical constituents of Salvia macrosiphon seeds as well as anti-inflammatory activities. Methods: The seed oil extracted via a Soxhlet extractor was subjected to pharmacognostic assays using High Performance Thin Layer Chromatography (HPTLC), Gas chromatography/mass spectrometry (GC/MS) analysis of fatty acids and sterols as well as evaluation of the possible anti-inflammatory activities in rats. Results: Total ash, acid insoluble and water soluble ash values were determined as 51.67±7.53, 10.00±0.02 and 30.01±5.01 mg/g, respectively. HPTLC assessment revealed the presence of different steroids, triterpenes and fatty acids. Amount of sterols in oil was found 2.44, 24.92 and 4.60 mg/g for esterified β-sitosterol, free β-sitosterol and free stigmasterol, respectively. The α-linolenic acid (77.69±6.10%) was the principal fatty acid. Regarding the anti-inflammatory activity, the seed oil showed low activity in the early phase of formalin test; however, could not significantly inhibit the neutrophil-induced damage by reducing MPO activity in the paws of the rat. Conclusion: The seed oil did not exhibit satisfactory effects on acute inflammation in this study but considering the rich phytosterols content, the seed and its oil can be introduced as useful dietary supplements.